Pengaruh Karakteristik Gamifikasi terhadap Niat Penggunaan Ulang Aplikasi Pembelajaran Seluler melalui Pemenuhan Kebutuhan Keterkaitan Karyawan - Windharti Amelia; Puji Asmoro; Gunawan Wibisono; Tengku Mohd. Khairal Abdullah (Syntax Literate, 2023)
Advances in communication technology also have an impact on learning where learning media is increasingly shifting towards online learning with mobile devices. Today, some companies are starting to apply the concept of gamification or the use of game characteristics on mobile learning applications to foster a positive impact on employee learning. The application of several gamification characteristics such as points, leaderboards, challenging content, and attractive graphic visuals is applied to mobile learning applications with the aim of motivating employees to continue learning activities using the application. This study aims to determine the impact of using game characteristics on mobile learning applications on the intention to reuse these applications. The survey was conducted on 112 employees of PT Jasa Marga who are users of the company's internal gamification-based mobile learning application. The results showed that gamification characteristics positively affect the intention of sustainable use. Meeting the satisfaction of basic needs of employee linkage also has a mediating effect on the intention of continuous use. The results of this study have significant implications in the development and application of gamification in employee learning applications to support organizational effectiveness